Menstrual phase effects on performance readiness in Division I women`s basketball: A longitudinal multi-modal study - Whitney, H. E.; Micir, A.; Ravi, R.; Seshadri, D. (International Journal of Exercise Science Conference Proceedings, 2025)
Hormonal changes across the menstrual cycle influence cardiovascular, neuromuscular, and recovery responses, potentially altering athletic readiness and injury risk. Despite this, cycle phases are rarely integrated into athlete monitoring. PURPOSE: To examine menstrual phase-related differences in physiological and psychological readiness in Division I women`s basketball players. METHODS: Thirteen NCAA Division I athletes (IRB #2113291-6) were tracked daily from October 2024 to April 2025. Subjective measures include energy, soreness, sleep quality, and stress. Workload metrics were collected with the Beyond Pulse platform, and biometric data (recovery score, sleep index, resting heart rate, heart rate variability) were obtained from the Ultrahuman Ring AIR. Menstrual phase was assigned by daily yes/no self-report of menstruation; no additional phase labels or contraception/cycle-regularity adjustments were used. The merged dataset included 2,742 entries, with 211 complete cases. Analyses used within-athlete, covariate-adjusted models (game/practice, within-athlete workload, and month fixed effects) comparing menstruation versus non-menstruation days. RESULTS: During menstruation at the team level, recovery score increased (+7.1%, ß=+5.29, p<0.001) and resting heart rate decreased (-3.3%, ß=-1.64 bpm, p=0.002). Sleep tended to be higher (+4.5%, ß=+3.58, p=0.100), while heart rate variability (ß=-0.70 ms, p=0.577), workload (ß=-0.24, p=0.577), top speed (ß=+0.12 m/s, p=0.353), and stress (Academic: ß=-0.01, p=0.960; Other: ß=+0.16, p=0.307) showed no meaningful change. CONCLUSION: In within-athlete, covariate-adjusted models, menstruation days were associated with greater physiological readiness (higher recovery and lower resting heart rate), while HRV, external load, top speed, and perceived stress did not differ significantly. Integrating menstrual tracking into athlete monitoring may improve recovery planning, performance optimization, and injury risk reduction.